Hepatoprotective effects of phloretin against CCl4-induced liver injury in mice. Issue 2 (4th March 2017) - Lu, Yalong; Chen, Jinwen; Ren, Daoyuan; Yang, Xingbin; Zhao, Yan
ABSTRACT: This study was designed to characterize the protective capacity of phloretin against acute liver oxidative injury induced by CCl4 in mice. Administration of phloretin at 100, 200 and 500 mg/kg·bw orally daily in mice for 21 consecutive days, prior to intraperitoneal injection of 0.5% CCl4 /peanut oil (ip, 0.3 mL), significantly reduced the CCl4-induced inhibition of serum alanine aminotransferase, aspartate aminotransferase and lactic dehydrogenase activities. Furthermore, phloretin elevated glutathione and superoxide dismutase activities and reduced formation of malonaldehyde in the liver of mice, when compared with CCl4 -intoxication mice. Moreover, phloretin also prevented the CCl4 -caused liver histological alteration, as indicated by histopathological evaluation. These data collectively demonstrated the potential prospect of phloretin as functional ingredient to prevent liver injury.